Clinical study on modified Shenzhe Zhenqi Decoction combined with ambroxol hydrochloride in the treatment of severe pneumonia - Xing, Binyu; Shen, Cunyi; Lin, Ting; Li, Xiaoning; Tan, Wenjun (Frontiers in Physiology, 2025)
ObjectiveThis study aimed to evaluate the clinical efficacy of modified Shenzhe Zhenqi Decoction combined with ambroxol hydrochloride in treating severe pneumonia.MethodsThis was a single-center, prospective, double-blind, randomized controlled trial. A total of 138 patients with severe pneumonia were randomly divided into two groups. The control group (n = 69) received ambroxol hydrochloride, while the observation group (n = 69) received modified Shenzhe Zhenqi Decoction combined with ambroxol hydrochloride. Clinical efficacy, Traditional Chinese Medicine symptom scores (fever, cough, expectoration, dyspnea), arterial blood gas indicators [oxygen saturation (SaO2), partial pressure of oxygen (PaO2), partial pressure of carbon dioxide (PaCO2)], lung function [forced expiratory volume in one second (FEV1), forced vital capacity (FVC), peak expiratory flow (PEF)], and inflammatory markers [interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α), C-reactive protein (CRP)] were evaluated. Adverse events were recorded for both groups.ResultsThe overall efficacy rates in the combined and control groups were 98.55% and 89.86% (P < 0.05). After treatment, in both groups, symptom scores for fever, cough, expectoration, and dyspnea were reduced, with the combined group showing more significant improvement; SaO2 and PaO2 levels increased, and PaCO2 decreased, with the combined group achieving greater improvement; FEV1, FVC, and PEF values increased, with higher values observed in the combined group; serum IL-6, TNF-α, and CRP levels decreased, with the combined group showing more substantial reductions (all P < 0.05). The incidence of adverse events was 4.35% in the combined group and 2.90% in the control group (P > 0.05).ConclusionModified Shenzhe Zhenqi Decoction combined with ambroxol hydrochloride demonstrated ideal clinical efficacy in treating severe pneumonia, alleviating symptoms and pulmonary inflammation and improving arterial blood gas indicators and lung function.